AUTO HI-IS: SOLUSI CERDAS BUDIDAYA JAMUR KONSUMSI DENGAN AUTOMATIC HUMIDITY SYSTEM - Budiman, Agus; Islami, Irfan (Program Kreativitas Mahasiswa - Karsa Cipta, 2014)
Â AUTO HI-IS is an automatic moisture control devices that are used as a solution in mushroom cultivation. During this time the mushroom growers of mushroom cultivation in regulating moisture they carry still use manual or conventional. It is very effective and efficient. Ineffective because by using the conventional way the farmers do not really know the exact humidity in the mushroom cultivation and moisture to be added. Inefficient due to the farmers using conventional means removing the power and the cost of production which will result in increased production costs. The design consists of a system of electronic devices, monitoring and planting medium. Electronic systems using the Arduino Nano microcontroller, sensors DHT11. Monitoring using a 16x2 LCD and a memory card that records the activities AUTO HI-IS. Growing media consisted of designing a shelf fungus as a mounting medium baglog and fogging. AUTO HI-IS be a smart solution mushroom cultivation consumption can regulate the temperature and humidity in the mushroom house automatically. Mushroom cultivators can be anywhere without being tied season. AUTO HI-IS into the realization of the automation system regulating the temperature and humidity in real form.Keywords: AUTO HI-IS, fungi, temperature, humidity, system.